Economic regulation of urban water and sanitation services : (World Bank, 2007)
This paper brings together key findings from the four pieces of work (Explanatory notes on key regulatory issues ; In-depth case studies on water sector regulation ; Guidelines for setting low-discretion rules ; review of regulation of publicly owned water and sanitation suppliers). It aims to show how real experience supports the theoretical principles of good design, and to present key regulatory concepts in way that is accessible to policy makers, service providers, non-governmental organizations, and other stakeholders concerned with improving the provision of water supply and sanitation services.